Time‐Resolved Potential‐Induced Changes in Fe/N/C‐Catalysts Studied by In Situ Modulation Excitation X‐Ray Absorption Spectroscopy. Issue 14 (21st February 2022) - Ebner, Kathrin; Clark, Adam H.; Saveleva, Viktoriia A.; Smolentsev, Grigory; Chen, Jingfeng; Ni, Lingmei; Li, Jingkun; Zitolo, Andrea; Jaouen, Frédéric; Kramm, Ulrike I.; Schmidt, Thomas J.; Herranz, Juan
Abstract: To advance the widespread implementation of electrochemical energy storage and conversion technologies, the development of inexpensive electrocatalysts is imperative. In this context, Fe/N/C‐materials represent a promising alternative to the costly noble metals currently used to catalyze the oxygen reduction reaction (ORR), and also display encouraging activities for the reduction of CO2 . Nevertheless, the application of these materials in commercial devices requires further improvements in their performance and stability that are currently hindered by a lack of understanding of the nature of their active sites and the associated catalytic mechanisms. With this motivation, herein the authors exploit the high sensitivity of modulation excitation X‐ray absorption spectroscopy toward species undergoing potential‐induced changes to elucidate the operando local geometry of the active sites in two sorts of Fe/N/C‐catalysts. While the ligand environment of a part of both materials' sites appears to change from six‐/five‐ to fourfold coordination upon potential decrease, they differ substantially when it comes to the geometry of the coordination sphere, with the more ORR‐active material undergoing more pronounced restructuring. Furthermore, these time‐resolved spectroscopic measurements yield unprecedented insights into the kinetics of Fe‐based molecular sites' structural reorganization, identifying the oxidation of iron as a rate‐limiting process for the less ORR‐active catalyst. Abstract : Studying two Fe/N/C‐catalysts with in situ modulation excitation X‐ray absorption spectroscopy, the authors resolve the kinetics of the Fe‐based sites' structural reorganization upon potential change and exploit the enhanced sensitivity of the technique toward species undergoing potential‐induced changes to elucidate the local geometry of a part of the active sites.